Patient-derived tau and amyloid-beta facilitate long-term depression in vivo: role of tumor necrosis factor alpha and the integrated stress response - Hu, NengWei; Ondrejcak, Tomas; Klyubin, Igor; Rowan, Michael (My University, 2024)
Alzheimer’s disease is characterized by progressive cognitive decline in older individuals accompanied by the deposition of two pathognomonic proteins amyloid β (Aβ) and tau. It is well documented that synaptotoxic soluble Aβ aggregates facilitate synaptic long-term depression (LTD), a major form of synaptic weakening which correlates with cognitive status in Alzheimer’s disease. Whether synaptotoxic tau, which also associates strongly with progressive cognitive decline in patients with Alzheimer’s disease and other tauopathies, also causes LTD facilitation remains to be clarified. Young male adult and middle-aged rats were employed. Synaptotoxic tau and Aβ were obtained from different sources including i) aqueous brain extracts from patients with Alzheimer’s disease and Pick’s disease tauopathy, ii) the secretomes of induced pluripotent stem cell (iPSC)-derived neurons from individuals with trisomy of chromosome 21 (Ts21), and iii) synthetic Aβ. In vivo electrophysiology was performed in urethane anesthetized animals. Evoked field excitatory postsynaptic potentials were recorded from the stratum radiatum in the CA1 area of the hippocampus with electrical stimulation to the Schaffer collateral-commissural pathway. To study the enhancement of LTD, relatively weak low-frequency electrical stimulation was used to trigger peri-threshold LTD. Synaptotoxic forms of tau or Aβ were administered intracerebroventricularly. The ability of agents that inhibit the cytokine tumor necrosis factor α (TNFα) or the integrated stress response to prevent the effects of Aβ or tau on LTD were assessed after local or systemic injection, respectively. We found that diffusible tau from Alzheimer’s disease or Pick’s disease patients’ brain aqueous extracts or the secretomes of Ts21 iPSC-derived neurons, like Alzheimer’s disease brain-derived Aβ and synthetic oligomeric Aβ, potently enhanced synaptic LTD in live rats. We further demonstrated that LTD facilitation by both tau and Aβ was age-dependent, being more potent in middle-aged compared with young animals. Finally, at the cellular level, we provide pharmacological evidence that the TNFα and the integrated stress response are downstream mediators of LTD facilitation by both synaptotoxic tau and Aβ. Overall, these findings reveal the promotion of an age-dependent synaptic weakening by both synaptotoxic tau and Aβ. Pharmacologically targeting shared mechanisms of tau and Aβ synaptotoxicity, such as TNFα/ the integrated stress response, provides an attractive strategy to treat early Alzheimer’s disease.
ACCEPTED
Keywords: Ageing; Neuroscience; Age related diseases; Ageing, memory and other cognitive processes; Neurodegeneration; Age-related disability; Mental Health/Psychosocial disability; Health